2012
DOI: 10.1128/aac.05490-11
|View full text |Cite
|
Sign up to set email alerts
|

Blood, Tissue, and Intracellular Concentrations of Erythromycin and Its Metabolite Anhydroerythromycin during and after Therapy

Abstract: For macrolides, clinical activity but also the development of bacterial resistance has been attributed to prolonged therapeutic and subtherapeutic concentrations. Although erythromycin is a long-established antimicrobial, concomitant determination of the pharmacokinetics of erythromycin and its metabolites in different compartments is limited. To better characterize the pharmacokinetics of erythromycin and its anhydrometabolite (anhydroerythromycin [AHE]) in different compartments during and after the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…In vivo studies provide an opportunity to evaluate drug distribution to the target site and the immune system's response to an infection. In human subjects, collection of plasma and microdialysis samples, coupled with isolation of white blood cells and subsequent determination of intracellular drug concentrations, provides an opportunity to assess tissue distribution in various compartments (68).…”
Section: Target Site Exposurementioning
confidence: 99%
“…In vivo studies provide an opportunity to evaluate drug distribution to the target site and the immune system's response to an infection. In human subjects, collection of plasma and microdialysis samples, coupled with isolation of white blood cells and subsequent determination of intracellular drug concentrations, provides an opportunity to assess tissue distribution in various compartments (68).…”
Section: Target Site Exposurementioning
confidence: 99%
“…Azithromycin concentrations in plasma, microdialysate, and WBC were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS) in analogy to a previously published method (29). The lower limit of quantification (LLOQ) for azithromycin was 1.00 ng/ml in plasma and 0.500 ng/ml for analyses of microdialysate and WBC samples, and interday precision and accuracy were 4.6 Ϯ 2.8% and 100.3 Ϯ 3.4% (plasma) and 6.6 Ϯ 1.2% and 98.0 Ϯ 4.3% (microdialysate and WBC).…”
Section: Regulatory Issuesmentioning
confidence: 99%
“…If withdrawal times for clearance of this antimicrobial are not strictly followed, excessive exposure to erythromycin and its metabolites to the GIT can occur, raising questions about potential effects on human health [9,10]. The PK/PD study revealed that erythromycin is metabolized into anhydroerythromycin (AHE) by gastric fluids [11]. The hydrolysis mechanism is more effective in acidic conditions compared to neutral or basic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrolysis mechanism is more effective in acidic conditions compared to neutral or basic conditions. Erythromycin and AHE are differentially distributed in blood, tissue, and leukocytes during and following therapy [11]. A detectable concentration of erythromycin was present in these sites/cells 72 h after the treatment; however, the proportion of AHE becomes higher after the end of treatment.…”
Section: Introductionmentioning
confidence: 99%